ANALISIS FAKTOR DOMINAN YANG BERHUBUNGAN DENGAN KEPATUHAN PEMERIKSAAN Antenatal Care DI WILAYAH KERJA PUSKESMAS DELI TUA TAHUN 2024 - Ariani, Peny; Wahyuni, Tifani Hadi Tri; Andriani, Andriani; Tampubolon, Elmina (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
Antenatal Care (ANC) is the visit of pregnant women to health care facilities to receive ANC services according to established standards. The Antenatal Care coverage in the working area of Deli Tua Community Health Center in 2023 was K1 = 73.2% and K6 = 68.8%, while the target was 85%. There were 5 dominant factors causing non-compliance with ANC examination, namely age, education, attitude, knowledge, and husband's support. Theaims of the study is to examine the relationshipbetween five dominant of the factors and the Examination Compliance The Antenatal Care which the factor ofthe most related to The Antenatal Care Examination Compliance. The type of the research used analytic survey with a cross-sectional design. The data of the analysis used chi-square test and binary logistic regression with a sample size of 94 pregnant women who met the inclusion criteria. The results of the study has been known that the dominant factors related toThe Antenatal Care Examination Compliance are knowledge and husband's support, while the dominant factors not related toThe Antenatal Care Examination Compliance were age, education, and attitude, and the most related dominant factor to The Antenatal Care Examination Compliance in the working area of Deli Tua Community Health Center was knowledge with (p = 0.000) and (aRP = 5.211-132.401). From the results of the study, it is recommended to health workers at Deli Tua Community Health Center to increase the intensity of providing information and education to pregnant women and their companions through counseling activities.